(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
We know that the whole nation suffers from lack of water, that is, the island, which is our water supply, is drying up day by day, and as a result of this, various accidents and air pollution have consequences such as lack of water. Given